Turning constraints into resources: the experience of TRAIN4M&H training program on migrants' health. (30th September 2020) - Declich, S; DePonte, G; Russo, M L; Marchetti, G; Dente, M G; Punzo, O; Marceca, M
Abstract: Background: The tender TRAIN4M&H (Provision of training for first-line health professionals and law enforcement officers working at local level with migrants and refugees, and training of trainers- contract 20167204), funded by the EC-DG SANTE under the 3rd EU HP, intended to conduct training programme in all EU/EEA countries for health professionals, law enforcement officers an social workers in front-line countries and coach trainers in the others. Objectives: Training was aimed at reinforcing skills, improving understanding and positive attitudes, and promoting a holistic approach in the work with migrants. The boundaries set by the tender included a short training duration; exclusive use of pre-existing and validated training materials; different professional targets. Italian National Health Institute and Sapienza University of Rome designed the training programme. Criteria for content selection and methodological choices were submitted for consultation to an inter-professional Expert Group in two steps. Results: Given the limited training timeframe, the delivery of specialised content could not be the focus of this training. It was decided therefore to transform the target requirement into added value, by mixing the target groups into multi-professional classes. This bring a diversity of understandings into the classroom and enhance communication between sectors. The training included also topics such as "context of migration" and "intercultural competences" to create common ground for multi-professional exchange. Similarly, the need to adapt to different EU/EEA contexts argued for a modular structure where Units are selected by the Local Trainer based on a training needs assessment questionnaire sent to trainees beforehand. All materials are on EU Health Policy Platform's Agora (webgate.ec.europa.eu/hpf/). Conclusions: Training on migrants' health is a complex process, requiring the engagement of learners from their previous experiences and an interdisciplinary approach. Key messages: Inter-professional training programme can be used for the adult trainings especially in case of a cross-sectoral topic as migrants' health is. Inter-professional training is a strategy that can guide coherently content design, outcome identification and the choice of evaluations tools.